1998
DOI: 10.1021/jp983144x
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Study on the Quenching Mechanism by Oxygen of the Lowest Triplet State in Solution

Abstract: The mechanism for the quenching by oxygen of the lowest triplet state (T1) of 9-acetylanthracene(ACA) in five saturated hydrocarbon solvents at pressures up to 400 MPa was investigated. The quenching rate constants of the T1 state of ACA, k q T, decrease monotonically with increasing pressure, and the apparent activation volumes for k q T vary in the range 0.8−5.3 cm3/mol. It was also found that the plots of ln k q T against ln η, where η is solvent viscosity, show significant downward curvatures in all the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 42 publications
6
54
0
Order By: Relevance
“…In our previous works,11,16 we measured the apparent activation volume, from the pressure dependence of *V q E at 25 ¡C. The values of are summarized in Table 1, k q *V q E together with those of the activation volume, deter- mined from the pressure dependence of the solvent viscosity.11, 16 The signiÐcant di †erence between and *V q E *V i E was attributed to the contribution of di †usion to the quenching.11 In agreement with the conclusion from the high pressure study, the present results from the temperature variable study suggest that the quenching is not fully but nearly di †usion-controlled.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In our previous works,11,16 we measured the apparent activation volume, from the pressure dependence of *V q E at 25 ¡C. The values of are summarized in Table 1, k q *V q E together with those of the activation volume, deter- mined from the pressure dependence of the solvent viscosity.11, 16 The signiÐcant di †erence between and *V q E *V i E was attributed to the contribution of di †usion to the quenching.11 In agreement with the conclusion from the high pressure study, the present results from the temperature variable study suggest that the quenching is not fully but nearly di †usion-controlled.…”
Section: Resultsmentioning
confidence: 98%
“…3 and 4 show the plots of against cg/T obtained by c/k q changing the temperature at 0.1 MPa, together with the results obtained by changing the pressure at 25 ¡C. 16 It can be seen that the plots bend slightly downward, especially in MCH, and also that they are approximately on a smoothed line in n-hexane and MCH, respectively. In the previous work,9 it was found that the plot using eqn.…”
Section: Determination Of and K Diff K Bimmentioning
confidence: 88%
See 2 more Smart Citations
“…
The lifetime of singlet oxygen ( 1 D g ) sensitized by apparently non-fluorescent 9-acetylanthracene (ACA) was determined at pressures up to about 35 MPa in supercritical ethane (SCF ethane;35, 45 and 55 C) as well as in liquid ethane (25 C) from the phosphorescence decay measurements. For all the systems examined, the decay rate constant (t D À1 ) increased significantly at the lower pressure region and monotonically as pressure increased further.
…”
mentioning
confidence: 99%